3l+6=p

Simple and best practice solution for 3l+6=p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3l+6=p equation:


Simplifying
3l + 6 = p

Reorder the terms:
6 + 3l = p

Solving
6 + 3l = p

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 3l = -6 + p

Combine like terms: 6 + -6 = 0
0 + 3l = -6 + p
3l = -6 + p

Divide each side by '3'.
l = -2 + 0.3333333333p

Simplifying
l = -2 + 0.3333333333p

See similar equations:

| 2(y-5)-5=3 | | (x/4)-2x=2 | | (27/3)=-8x | | 576=(3x+20)+5(.65x)+(.5x) | | 576=(3x+20)+5(.65x)+(.5x) | | Y=3y-a | | 3(3p+4)-4(p+8)= | | 16x+24=16x+24 | | .25(3x-16)+.25x=5.333 | | -2.3-3y-2.5-y=-3y-3.6 | | 4(x+3)=2x+74 | | Log(x+3)=2.1 | | 78+2x=100 | | 6(3b-8)=2(6b-3) | | 15+3m=27 | | -6.3-3z-1.5-z=-3z-5.9 | | 4b+b^2=0 | | -1x^1+1= | | .20x+.35(30)=29.5 | | 4(x-10)=-6(x-2)-6 | | (-2a/b^4)^2 | | .20+.35(30)=29.5 | | y=x^2+2ax+4 | | .355=(×^×)/((2.82-2×)(2.83-2×)(2.83-×) | | -46+34= | | (3/10)-3 | | 62=6x-10 | | f(3)=0/21= | | 27x^2+3x-10= | | 7x-(3x+2)=62 | | 8/5m=4/15 | | 45/?=13 |

Equations solver categories